2020
DOI: 10.7454/jki.v0i0.1095
|View full text |Cite
|
Sign up to set email alerts
|

Peer Support and Family Acceptance with Quality of Life of MSM Living With HIV and Antiretroviral

Abstract: Men who have sex with men (MSM) comprise a population at risk for HIV infection. Quality of Life (QOL) becomes the main goal to lengthen their life span. This study was conducted to determine the relationship between peer support and family acceptance toward QOL of MSM living with HIV and ARV in Medan. A total of 175 respondents were involved in this cross-sectional study that was carried out via purposeful sampling. Data were collected by means of the Perceived Acceptance Scale, Peer Group Caring Interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…19,20 Similarly, studies with MSM living with HIV have reported that their better acceptance of the illness, family acceptance and peer support are positively associated with their better QoL. [21][22][23][24] Despite a range of factors associated with poor or good QoL of PLHIV as reported in the aforementioned studies, none of these studies reported a comparison of QoL of MSM living with HIV and non-MSM living with HIV or heterosexual men globally. In the context of Indonesia, there is limited evidence on and studies exploring the QoL of different populations groups living with HIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Similarly, studies with MSM living with HIV have reported that their better acceptance of the illness, family acceptance and peer support are positively associated with their better QoL. [21][22][23][24] Despite a range of factors associated with poor or good QoL of PLHIV as reported in the aforementioned studies, none of these studies reported a comparison of QoL of MSM living with HIV and non-MSM living with HIV or heterosexual men globally. In the context of Indonesia, there is limited evidence on and studies exploring the QoL of different populations groups living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Indonesia, there is limited evidence on and studies exploring the QoL of different populations groups living with HIV. 21,[23][24][25] Therefore, this study aimed to compare the QoL of men living with HIV with different sexual orientations and determine the dominant factors that affect their QoL.…”
Section: Introductionmentioning
confidence: 99%